Akutna ledvična odpoved ob zlorabi kokaina - Hojs, Nina (Medicinski razgledi, 2011)
Acute renal failure is characterised by a rapid decline in glomerular filtration rate over hours to days. Causes of acute renal failure are varied and include cocaine abuse. Cocaine can lead to acute renal failure directly (via vasoconstriction) or indirectly (via rhabdomyolysis). The paper presents the case of a 29 year old man with acute renal failure due to rhabdomyolysis, direct effects of cocaine, alcohol abuse and dehydration. Rhabdomyolysis probably occurred due to muscle compression, cocaine and alcohol abuse. The patient needed dialysis.
Keywords: Acute Kidney Injury; Ledvica, akutna poškodba; Motnje zaradi kokaina; Cocaine-Related Disorders; Rabdomioliza; Rhabdomyolysis; ledvice; akutna ledvična odpoved